HOW GLOBALIZATION AND TECHNOLOGY SHAPE LANGUAGE IN THE 21ST CENTURY - Adxamov Shoxruh Abdurashid o`g`li (Bright Mind Publishing, 2025)
This article talks about how globalization, technological progress, and language change are all connected and changing all the time in the 21st century. It focuses on language borrowing and innovation. Languages around the world have added new words and phrases to fit modern ideas and tools. This process has been sped up by cultural exchange, economic dependency, and fast digital communication. As the most common language in the world, English is a major source of loanwords that affect languages like Spanish, Uzbek, and Japanese. The study talks about some of the main things that cause people to take languages, such as media exposure, global cultural integration, and new technologies. It also looks at how technology encourages the use of neologisms and hybrid languages. The effects of these changes are talked about, weighing the pros and cons of better global contact with worries about the loss of cultural identity and linguistic heritage. To make sure that language stays both a way for people around the world to communicate and a place where cultural heritage is kept, it is important to find a balance between progress and preservation.
Keywords: Globalization, linguistic borrowing, language evolution, technology, neologisms, hybrid language, cultural exchange, digital communication, language preservation, linguistic identity.